Grey systems theory in economics – bibliometric analysis and applications' overview. Issue 2 (3rd August 2015) - Delcea Camelia, Professor; Camelia, Delcea
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to synthesize the review of the existing literature attached to the grey economic system theory and applications and aims to offer a comprehensive picture of the contribution brought by the researchers to this particular field. Also, the paper underlines the main research areas within the grey economic theory and applications and serves as an informative summary kit for future research works and research directions. Design/methodology/approach – For appreciating the scientific progress made since the grey systems theory has been initiated to the present, with an accent on the literature dedicated to the economic field, a bibliometrics analysis has been conducted. The Perish or Publish software was used for extracting the needed data from Google Scholar for the entire period since the appearance of grey systems to now-a-days. In addition, an ISI Web of Science (WoS) search has been performed for extracting the grey economic papers. As the main focus is on the economic subject area of the grey systems, only the papers related to this field have been selected. Findings – The total number of grey economic paper from both Google Scholar and ISI WoS database, the number of authors, some citation metrics, H-index, authors' provenience country, papers' language, etc., have been presented and analysed. Also, a list with the most cited papers in the grey economic relational analysis, grey economic prediction models and grey economic incidence is putted forward. Practical implications – Through the bibliometric analysis on grey economic papers written over time, a qualitative analysis was performed on this field in order to underline the main research direction, to analyse what has been done in this field and to determine which can be the next research directions that can emerge from here. Originality/value – The paper succeeds in enlarging the view regarding the usage of grey systems theory in the economic field, offering a suitable analysis on the considered areas. Even though bibliometrics analysis have been conducted on the grey systems theory field, a grey economic bibliometric analysis has not been done yet, to the authors' knowledge. Therefore, a synthesized of the existing literature attached to the grey economic system theory and applications is presented in order to offer a more comprehensive picture of the contribution brought by the researchers to this particular field.